“Chapter 5. Microwave Energy and Light Energy Transformation: Methods, Schemes and Designs” - Frolova, T. I.; Churyumov, G. I. (InTech, 2018)
Nowadays, electrodeless sulfur lamps with microwave excitation (ESLME) are finding ever-widening application in energy-efficiency lighting systems. A reason of increased interest to these lamps is due to high values of their parameters including a high light flux (120-145 klm), a light intensity (~ 9000 cd), a high value of light output (80-110 lm/W), color rendition coefficient (Ra ~ 90), as well as an application of environmentally friendly materials (argon and sulfur). This chapter presents a novel approach of creating an energy-efficiency lighting source on the basis of the ESLME. For an electrodynamic structure of the lighting system, one can propose to use an optically transparent (mesh) waveguide instead of a microwave cavity. It is shown that the use of proximity of the spectra of optical radiation generated by the sulfur lamp and solar radiation allows more efficiently (in comparison with other light sources) their application as the simulators of sunlight for testing photoelectric converters and solar cells. For extending application of the lighting systems on the basis of the sulfur lamp and further increasing an energy efficiency of these systems, their integration with other electron devices (for example, solar cells) is proposed.
Keywords: lighting system; electrodeless sulfur lamp; magnetron; electromagnetic field; microwave excitation